PHENOMENOLOGICAL STUDY OF INTERPERSONAL COMMUNICATION AND THE RESILIENCE OF ADOLESCENT VICTIMS OF PARENTAL DIVORCE - Karina Jayanti; Fitri Dwi Lestari (Universitas Gunadarma, 2022)
Divorce cases are a common occurrence in society. Disputes and constant fights are the highest factor in divorce in 2021, namely 279,205 cases. Divorce can have an impact on communication, psychological, behavioral, social, and academic problems in children. The reduced intensity of children's communication with parents will make children look for figures who are able to provide direction on how to interact and socialize with their environment. Many teenagers with divorced parents have a life that is down and not good. Resilience is defined as the ability to recover from difficulties and changes that have occurred to previous functions and move forward towards improvement. The purpose of this study is how interpersonal communication and resilience of a teenager who experienced a state of parental divorce. This study uses a qualitative method with a phenomenological approach. This study uses interpersonal communication theory with the basic assumption that everyone who communicates will make predictions on psychological data about the effects or behavior of the communication, namely how the party receiving the message reacts. From the results of the research and discussion that has been carried out, it can be concluded that the three adolescent informants who are victims of parental divorce over time, they are able to communicate interpersonally and provide opportunities for someone to talk about themselves, with other people, get to know and understand themselves. themselves and understand their own attitudes and behavior. the three informants can also be said to be resilient, despite experiencing the impact of their parents' divorce. This is because the three informants have sources of building resilience that interact with each other and can support one another, so that there appears to be a balance between the impacts generated and the resources they have. Besides that, the sources owned by all informants are included in the profile of resilient youth.